Entrepreneurial Pedagogy: An Example of Using Student-Developed Case Studies - Anna Dębicka; Karolina Olejniczak (Jesuit University Ignatianum in Krakow, 2020)
RESEARCH OBJECTIVE: The article attempts to explain the benefits that may result from the use of case studies developed by students as a teaching method applied in entrepreneurial pedagogy. THE RESEARCH PROBLEM AND METHODS: The main research problem concerns the effectiveness of using case studies created by students as a teaching method in entrepreneurial pedagogy. The article provides an overview of selected literature and presents the authors' experience in applying student-developed case studies. THE PROCESS OF ARGUMENTATION: In the first part of the article, the most important entrepreneurial skills and competences are discussed. Subsequently, the importance of using activating methods is presented, with particular emphasis on the case study. In the second part, the use of the case study developed by students was analyzed and evaluated. Finally, the conclusions and recommendations are presented. RESEARCH RESULTS: The literature analysis indicates the importance of methods that foster students' active involvement, including case studies, in entrepreneurial pedagogy. The analysis of case studies developed by students showed their strong commitment to the assignment. Students had to gain knowledge of the operation of enterprises and the processes that take place in them. In addition, the task required students to be familiar with methods and tools that support creative thinking and problem-solving skills. CONCLUSIONS, INNOVATIONS, AND RECOMMENDATIONS: Based on the analysis of literature and student-developed case studies, it seems that the discussed method is an effective teaching method that increases students' commitment to the assignment and supports the development of entrepreneurial attitudes and skills. Furthermore, this method provides a range of benefits that give the teacher great freedom in choosing the issues and scope of case studies created by students. The results of the analysis permit concluding that student-developed case studies can be commonly used and allow developing a wide range of students entrepreneurial skills.